Pengaruh Model Pembelajaran Role Playing Terhadap Hasil Belajar PPKN Siswa Kelas IV SDN 091287 Panei Tongah - Fani Frida Yanti Tambunan; Theresia Monika Siahaan; Esti Sirait (JOURNAL SAINS STUDENT RESEARCH, 2023)
The aim of this research is to determine the influence of the ROle Playing learning model on the PPKN learning outcomes of class IV students at SD Negeri 091287 Panei Tongah. There are 2 hypotheses in this research, namely 1. There is an influence of the role playing learning model on the learning outcomes of students at SD Negeri 091287 Panei Tongah, 2. There is no influence of the role playing learning model on the learning outcomes of students at SD Negeri 091287 Panei Tongah.This research uses an experimental method with a pre-experimental design research method. The population of this study was all 22 grade IV students at SD Negeri 091287 Panei Tongah.Data collection was carried out using test administration techniques. The tests used are pretest and posttest. Based on data analysis, it is known that the t calculated result is 11.68 with a significance level of 0.05. So it can be